Marine propellers and propulsion - Carlton, J. S. (Butterworth-Heinemann, an imprint of Elsevier, 2007)
Marine Propellers and Propulsion, Fourth Edition offers comprehensive, cutting edge coverage to equip marine engineers, naval architects or anyone involved in propulsion and hydrodynamics with essential job knowledge. Propulsion technology is a complex, multidisciplinary topic with design, construction, operational and research implications. Drawing on experience from a long and varied career in consulting, research, design and technical investigation, John Carlton examines hydrodynamic theory, materials and mechanical considerations, and design, operation and performance. Connecting essential theory to practical problems in design, analysis and operational efficiency, the book is an invaluable resource, packed with hard-won insights, detailed specifications and data